Magnetostratigraphic age and monsoonal evolution recorded by the thickest Quaternary loess deposit of the Lanzhou region, western Chinese Loess Plateau. (1st May 2016) - Zhang, Jun; Li, Jijun; Guo, Benhong; Ma, Zhenhua; Li, Xiaomiao; Ye, Xiyan; Yu, Hao; Liu, Jia; Yang, Cheng; Zhang, Shengda; Song, Chunhui; Hui, Zhengchuang; et al.
Abstract: The loess-paleosol sequences of the Chinese Loess Plateau (CLP) are major paleoclimatic archives which document the evolution of the East Asian Monsoon (EAM) and changes in the Northern Hemisphere ice sheets during the Quaternary glacial-interglacial cycles. However, the mechanisms regulating the trend of EAM variations on a tectonic scale are unclear. The loess deposits of the western CLP, which have a close relationship with tectonics and climate, are much better-suited to exploring these mechanisms than those of the central CLP. However, studies of long-term EAM evolution from the western CLP have been hindered by the lack of long, accurately-dated sequences with high sediment accumulation rates. Here, we address this problem via high resolution magnetostratigraphic, magnetic susceptibility and grain-size analyses of a 416.2 m-long drill core located at Xijin Village, near Lanzhou. Paleomagnetic dating indicates that the basal age of the Xijin loess is ∼2.2 Ma. The χ and grain-size records reveal that the East Asian Summer Monsoon (EASM) and East Asian Winter Monsoon (EAWM) strengthened synchronously at ∼1.24 Ma. Subsequently, during interglacial periods, the EASM began to penetrate, and then dominate, in the Lanzhou region. This was followed by two stepwise uptrends, commencing at ∼0.87 and ∼0.62 Ma, which resulted in an increasingly moist interglacial climate in the region. We suggest that the uplift of the Tibetan Plateau was largely responsible for these three stepwise enhancements of the EASM. Overall, however, the long-term trend of strengthening in EAWM in the area may have been primarily caused by long-term global cooling from the Late Pliocene onwards. Highlights: The Xijin loess core in Lanzhou was found to bear 46 paleosol layers. The thickest loess in Lanzhou was initially dated to 2.2 Ma. Uplift of Tibetan Plateau drove three stepwise uptrends of the EASM. The strengthening of the EAWM was mainly affected by global cooling.